Pengaruh Faktor Sosio-ekonomi dan Teknis Terhadap Hasil Tangkapan Nelayan Skala Kecil - Alimudin Laapo; Aisah Aisah; Karlina Muhsin Tondi (Musamus Fisheries and Marine Journal, 2021)
The fish catch by fishermen on the coast of Donggala Regency tends to fluctuate and is relatively low. This is thought to be caused by social, economic and traditional fishing techniques. This study analyzes the influence of fishermen experience factors, operational cost, fishing ground distance, long time at sea, and machine power on the fish catch of small-scale fishermen in Donggala Regency. Data collection was carried out from November 2020 to January 2021, and was analyzed using the Multiple Linear Regression method. The findings indicate that the fish catches of fishermen are influenced by the five socio-economic and technical factors analyzed. Capture fisheries development policies need to pay attention to the availability of capital, ownership and mastery of fishing technology.